2016
DOI: 10.1007/s10549-016-4050-2
|View full text |Cite
|
Sign up to set email alerts
|

The presence and impact of estrogen metabolism on the biology of triple-negative breast cancer

Abstract: Overall this study suggests the presence of, and a potential protective effect of estrogens in TNBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…43 However, McNamara et al demonstrated that enzymes known to modulate levels of estrogens were detected in TNBC and were associated with longer disease-free survival, suggesting the presence of, and a potential protective effect of estrogens in TNBC. 44 Current findings speculate the effect of estrogen in TNBC may be mediated by other activating effectors related to ER signaling or other receptors. Consistent with previous studies, 19,20 we observed that high expression of ERRα was associated with aggressive clinicopathologic features in TNBC, including high NG, frequent LNM, and advanced TNM stage, as well as poor survival outcomes.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…43 However, McNamara et al demonstrated that enzymes known to modulate levels of estrogens were detected in TNBC and were associated with longer disease-free survival, suggesting the presence of, and a potential protective effect of estrogens in TNBC. 44 Current findings speculate the effect of estrogen in TNBC may be mediated by other activating effectors related to ER signaling or other receptors. Consistent with previous studies, 19,20 we observed that high expression of ERRα was associated with aggressive clinicopathologic features in TNBC, including high NG, frequent LNM, and advanced TNM stage, as well as poor survival outcomes.…”
Section: Discussionmentioning
confidence: 90%
“… 43 However, McNamara et al demonstrated that enzymes known to modulate levels of estrogens were detected in TNBC and were associated with longer disease-free survival, suggesting the presence of, and a potential protective effect of estrogens in TNBC. 44 Current findings speculate the effect of estrogen in TNBC may be mediated by other activating effectors related to ER signaling or other receptors.…”
Section: Discussionmentioning
confidence: 90%
“…This is supported by the fact that HSD17B6 and ERβ are often colocalized in prostate tissue [101]. In triple negative breast cancer, it was shown to be associated with improved outcome, likely by promoting ERβ signaling [102]. …”
Section: Other Hsd17b Enzymesmentioning
confidence: 99%
“…Of note, isoflavones have several times higher affinity for ERβ than for ERα, therefore some selectivity in physiological activity among phytoestrogens can be expected [56]. However, some triple negative breast cancers exhibit active ERβ [57]. Some phytoestrogens interfere with steroid hormones biosynthesis; for example, dehydrogenases of 17β-hydroxysteroids, 3β-hydroxysteroids, and aromatase lowering testosterone and estradiol production [55].…”
Section: Enteric Microbes and Phytoestrogensmentioning
confidence: 99%